1995
DOI: 10.1161/01.atv.15.12.2200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Elastin-Degrading Activity and Neointimal Formation in Porcine Aortic Organ Culture

Abstract: We investigated the association between tissue elastolytic activity and the development of neointimal formation using a previously described porcine aortic organ culture. Neointimal formation is associated with the presence of intact endothelium (nondenuded cultures) but is markedly reduced if endothelial cells are removed (denuded cultures). In nondenuded organ cultures, elastolytic activity assessed by using [3H]elastin increased sixfold at day 3 after initiation of the culture (P < .01), a time earlier than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In this study we adapted an organ culture system used previously to show the development of a neointima in porcine aorta in association with SMC proliferation (35). Those studies showed that the mechanism of SMC proliferation is likely related to serine elastase activity (11). Serine elastases are known to stimulate SMC proliferation by releasing growth factors such as FGF-2 from ECM proteoglycans (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we adapted an organ culture system used previously to show the development of a neointima in porcine aorta in association with SMC proliferation (35). Those studies showed that the mechanism of SMC proliferation is likely related to serine elastase activity (11). Serine elastases are known to stimulate SMC proliferation by releasing growth factors such as FGF-2 from ECM proteoglycans (10).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors were chosen to target MMPs or the heightened elastase activity demonstrated in Mctinduced vascular disease (8,18,21,22). Doses were based upon our previous studies (11,18,23).…”
Section: Experimental Designsmentioning
confidence: 99%
“…We have shown increased activity of a serine elastase of similar molecular weight in coronary arteries of piglets after experimental induction of the postcardiac transplant arteriopathy (29). Increased activity of a serine elastase is also present in aorta organ culture in association with the development of neointimal formation (30). In the clinical setting, increased elastolytic activity has also been described in atherosclerosis (11) and in a vasculopathy induced by actinic radiation (31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of theses studies suggest that release of elastase activity, in a porcine aortic organ culture model, was associated with intimal smooth muscle cell proliferation and intimal hyperplasia. 20 In this model, the inhibition of elastase activity with ␣ 1 -proteinase inhibitor markedly repressed the proliferation of neointimal smooth muscle cells. 20 Elastase inhibitors might also prevent the development of coronary artery disease experimentally induced after heart transplantation and intimal hyperplasia after balloon angioplasty in rabbits.…”
Section: Discussionmentioning
confidence: 79%
“…20 In this model, the inhibition of elastase activity with ␣ 1 -proteinase inhibitor markedly repressed the proliferation of neointimal smooth muscle cells. 20 Elastase inhibitors might also prevent the development of coronary artery disease experimentally induced after heart transplantation and intimal hyperplasia after balloon angioplasty in rabbits. 21,22 Several Japanese studies have been investigated the effects on atherosclerosis of an oral drug containing porcine pancreatic elastase 1.…”
Section: Discussionmentioning
confidence: 79%